You are on page 1of 2

𝒂 𝒃

|A|=[ ]=(a*d)-(b*c)
𝒄 𝒅
𝒂 𝒃 𝒄 𝒂 𝒃 −
|A|=[ 𝒅 𝒆 𝒇 ] [𝒅 𝒆 ]
𝒈 𝒉 𝒊 𝒈 𝒉 +

Cramer
𝒂 𝒃 𝒄𝒋𝟏
(𝒅 𝒆 𝒇𝒋𝟐)=|A|
𝒈 𝒉 𝒊 𝒋𝟑

𝒋𝟏 𝒃 𝒄 𝒂 𝒋𝟏 𝒄 𝒂 𝒃 𝒋𝟏
|A1|=(𝒋𝟐 𝒆 𝒇 ) |A2|=(𝒅 𝒋𝟐 𝒇) |A3|=(𝒅 𝒆 𝒋𝟐) 𝒙 |𝑨𝒏|
𝒋𝟑 𝒉 𝒊 𝒈 𝒋𝟑 𝒊 𝒈 𝒉 𝒋𝟑 𝒏=
|𝑨|

𝒂 𝒃 𝒄𝒅 𝒋𝟏
𝒆 𝒇 𝒈𝒉 𝒋𝟐
( )=|A|
𝒊 𝒋 𝒌𝒍 𝒋𝟑
𝒎 𝒏 𝒐𝒑 𝒋𝟒

𝒇 𝒈 𝒉 𝒆 𝒈 𝒉 𝒆 𝒇 𝒉 𝒆 𝒈 𝒉 −
|A| =a [ 𝒋 𝒌 𝒍 ]-b⌊ 𝒊 𝒌 𝒍⌋ + c ⌊ 𝒊 𝒋 𝒍 ⌋- d ⌊ 𝒊 𝒌 𝒍⌋
𝒏 𝒐 𝒑 𝒎 𝒐 𝒑 𝒎 𝒏 𝒑 𝒎 𝒐 𝒑 +

inversa

𝒂𝒙 𝒃𝒚 𝒄𝒛𝒋𝟏
( 𝒅𝒙 𝒆𝒙 𝒇𝒛𝒋𝟐)=|A|
𝒈𝒙 𝒉𝒙 𝒊𝒛 𝒋𝟑

𝒂 𝒃 𝒄
[ 𝒅 𝒆 𝒇 ]= A
𝒈 𝒉 𝒊
𝒂 𝒃 𝒄 𝒂 𝒃 −
|A|=[ 𝒅 𝒆 𝒇 ] [𝒅 𝒆 ]
𝒈 𝒉 𝒊 𝒈 𝒉 +

𝒂 𝒃 𝒄
𝒆 𝒇 ]= [ 𝒆 𝒇 ] - [
𝒅 𝒇 𝒅 𝒆 𝒃 𝒄 − 𝒄𝟏 𝒄𝟐 𝒄𝟑
AC =[ 𝒅 ] + [ ]-[ ] =[ 𝒄𝟒 𝒄𝟓 𝒄𝟔 ]
𝒉 𝒊 𝒈 𝒊 𝒈 𝒉 𝒉 𝒊 + 𝒄𝟕 𝒄𝟖 𝒄𝟗
𝒈 𝒉 𝒊

𝒄𝟏 𝒄𝟐 𝒄𝟑 𝒄𝟏 𝒄𝟒 𝒄𝟕 𝑨𝑻 = 𝑨𝒅𝒋𝑨(𝑨𝒄)= [ 𝒄𝟒 𝒄𝟓 𝒄𝟔 ]=[ 𝒄𝟐 𝒄𝟓 𝒄𝟖] 𝒄𝟕 𝒄𝟖 𝒄𝟗 𝒄𝟑 𝒄𝟔 𝒄𝟗 𝑪𝟏 𝑪𝟒 𝑪𝟕 |𝑨| |𝑨| |𝑨| −𝟏 𝑨𝒅𝒋𝑨 𝑪𝟐 𝑪𝟓 𝑪𝟖 𝒄𝟏 𝒄𝟒 𝒄𝟕 𝒄𝟐 𝒄𝟓 𝒄𝟖 𝑨 = = |𝑨| |𝑨| |𝑨| X= ( (𝒋𝟏) (𝒋𝟐) (𝒋𝟑)) Y= ( (𝒋𝟏) (𝒋𝟐) (𝒋𝟑)) |𝑨| |𝑨| |𝑨| |𝑨| |𝑨| |𝑨| |𝑨| 𝑪𝟑 𝑪𝟔 𝑪𝟗 (|𝑨| |𝑨| |𝑨|) 𝒄𝟑 𝒄𝟔 𝒄𝟗 Z= ( (𝒋𝟏) (𝒋𝟐) (𝒋𝟑)) |𝑨| |𝑨| |𝑨| 𝒂 𝒃 𝒄𝒅 𝒋𝟏 𝒆 𝒇 𝒈𝒉 𝒋𝟐 ( )=|A| 𝒊 𝒋 𝒌𝒍 𝒋𝟑 𝒎 𝒏 𝒐𝒑 𝒋𝟒 𝒂 𝒃 𝒄𝒅 𝒆 𝒇 𝒈𝒉 ( )=A 𝒊 𝒋 𝒌𝒍 𝒎 𝒏 𝒐𝒑 𝒇 𝒈 𝒉 𝒆 𝒈 𝒉 𝒆 𝒇 𝒉 𝒆 𝒈 𝒉 − |A| =a [ 𝒋 𝒌 𝒍 ]-b⌊ 𝒊 𝒌 𝒍⌋ + c ⌊ 𝒊 𝒋 𝒍 ⌋.d ⌊ 𝒊 𝒌 𝒍⌋ 𝒏 𝒐 𝒑 𝒎 𝒐 𝒑 𝒎 𝒏 𝒑 𝒎 𝒐 𝒑 + .